PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia Periode 2016 – 2020) - Ruth Theodora Liza; Daljono Daljono (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to examine return on assets affected good corporate governance that board of directors, independent board of commissioners, audit committee, managerial ownership, and institutional ownership on manufacturing companies. Variables used in the examination are board of directors, independent board of commissioners, audit committee, managerial ownership, institutional ownership, and also return on assets as the dependent variable.This research used manufacturing companies during the 2016-2020 with a total sample size of 210 samples. Sampling based on a purposive sampling method that follows certain criteria(s). Multiple linear regression analysis is the analysis method used in this research.The results of this study indicates that board of directors, independent board of commissioners, audit committee, institutional ownership have a positive significant effect on return on assets. Managerial ownership have no effect on return on assets.